Effects of Temperature and Aeration on The Dissolved Oxygen (DO) Values in Freshwater Using Simple Water Bath Reactor: A Brief Report - Febiyanto Febiyanto (Walisongo Journal of Chemistry, 2020)
This work investigated the effect of temperature and aeration treatments on the dissolved oxygen (DO) values in freshwater. The study was carried out using a simple water bath reactor in room temperature condition. Based on the results, freshwater sample without the aeration and temperature treatments (control) indicates a fluctuating profile on which the obtained values of DO were 4.21-4.98 mg/L at Taverage = 27.7 °C. However, the aeration treatment was slightly able to enhance the DO value up to 8.12 mg/L from the initial concentration of 3.88 mg/L at Taverage = 27.4 °C. Compared to the aeration treatment, the addition of temperature treatment has extremely increased the DO value up to 21 mg/L from 6.6 mg/L (T0 minutes = 27 °C)  for 20 minutes of DO observation (T20 minutes = 12.4 °C). Hence, this brief report suggests that the addition of temperature treatment gave a significant effect on the DO value in freshwater than the aeration treatment and control.